Penerapan Evidence Based Nursing Practice (EBNP) Edukasi Video 5 Pilar terhadap Kadar Glukosa Darah Pasien Diabetes - Hentu, Ardin Saleh; Irawati, Diana; Anggareni, Dewi; Jumaiyah, Wati; Abriyanti, Rika Mustika (Journal of Telenursing (JOTING), 2023)
This research aims to identify the effectiveness of 5 pillars of education in controlling blood sugar levels. The method used in EBNP is a case study design. The application of EBNP begins with an article search by selecting articles that use the RCT method with the keyword "Education Video IN DIABETIC PATIENTS." The results of this EBNP research show that education on applying the five pillars video effectively controls blood sugar levels with a p-value of 0.01. In conclusion, using the five pillars of teaching effectively prevents blood sugar levels in diabetes patients at Tarakan Regional Hospital, Jakarta. Keywords: EBNP, 5 Pillar Education, Blood Sugar